2016
DOI: 10.1039/c5cp04497a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sumanene modifications with boron and nitrogen atoms to its hydrogen adsorption properties

Abstract: We investigate the influence of sumanene modifications on its adsorption properties towards the hydrogen molecule. The benzylic positions of sumanene were substituted with boron and nitrogen atoms, which changed its hydrogen storage properties. H2 binding energies were calculated using the LMP2, DFT and DFT-D3 approaches with several exchange-correlation functionals and the results indicate a physisorption mechanism. Physisorption was confirmed by fragment analysis and special attention was paid to non-covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…69,71 Due to these unique properties, the adsorption of ions and molecules on C 21 H 12 has been widely studied. 69,71,[73][74][75][76][77][78][79][80][81] For example, Petrushenko et al found that Li + is more easily adsorbed on the concave surface of C 21 H 12 with an adsorption energy of À40.48 kcal mol À1 than on the convex surface. 71 Reisi-Vanani et al studied the adsorption of CO on Li + modified sumanene.…”
Section: à57mentioning
confidence: 99%
“…69,71 Due to these unique properties, the adsorption of ions and molecules on C 21 H 12 has been widely studied. 69,71,[73][74][75][76][77][78][79][80][81] For example, Petrushenko et al found that Li + is more easily adsorbed on the concave surface of C 21 H 12 with an adsorption energy of À40.48 kcal mol À1 than on the convex surface. 71 Reisi-Vanani et al studied the adsorption of CO on Li + modified sumanene.…”
Section: à57mentioning
confidence: 99%
“…On the other side the LMP2 level of theory is not available in many molecular modeling packages so we decided to calculate binding energies at the DFT/B3LYP-D3 level of theory as well, which is a level of theory that is readily available in all molecular modeling packages capable of dealing with DFT calculations and which is recommended in cases when noncovalent interactions take place. [53][54][55] Although the LMP2 and DFT levels of theory provide expectedly different values of binding energies, the trends are completely in agreement. According to the binding energies, the strongest interaction occurs in the case of the system consisting of the 4-L complex and cisp, with the corresponding binding energy of À64 kcal mol À1 at the LMP2 level of theory (À61 kcal mol À1 at DFT level of theory).…”
Section: Complexes As Carriers Of Cisplatinmentioning
confidence: 75%
“…For determining the most active reaction sites of the molecules of bis-benzoxazolylhydrazone 1 and its copper coordination compounds 2-5 the calculation of MEP (molecular electrostatic potential) and ALIE (average local ionization energy) surfaces was performed. MEP surface allows one to visualize the molecular sites, which are most suitable for the electrophilic and nucleophilic interactions, [81][82][83] because it is determined by the distribution of the surface electric charge of the molecule. Application of this analyses help to rationalize the interaction of the molecule with other substrates.…”
Section: Mep and Alie Surfacesmentioning
confidence: 99%